Rak požiralnika - Eržen, Janez (Medicinski razgledi, 2010)
Esophageal carcinoma is one of those malignant tumors which have the worst prognosis and exhibit a marked geographic variation in their incidence. While the incidence of esophageal squamous celI carcinoma has remained steady, an increasing incidence of adenocarcinoma has been observed over the past 3 decades in Europe and North America. The classic symptom of this disease is progressive dysphagia for solid food. Its clinical diagnosis is obtained from medical history, physical examination, and barium esophagography. The clinicaldiagnosis requires a histological confirmation using tissue obtained by flexible esophagoscopy. Various endoscopic procedures and surgical resections remain the mainstay of treatment for patients with localized tumors, but in an increasing number of cases various combinations of chemotherapeutic agents and radiation therapy are used.
Keywords: diagnostika; Požiralnik, novotvorbe; požiralnik; tumor; novotvorbe; rak (medicina); therapy; zdravljenje